The Library Supply Chain Model: A Brief Review - A. K. Mahbubul Hye; Engku M. Nazri; Nurakmal Ahmad Mustaffa (International Journal of Supply Chain Management, 2019)
The focus of this paper is to review previous works on library supply chain model towards recommendations for a framework on how to construct a library supply chain model. Thus, the aspects that relate to the objective of how to model the library supply chain were reviewed. These include all the important literature to support the required information for the library supply chain model such as the members/entities of a library supply chain model, the structural dimensions of a library chain network, and the different types of process links across a library supply chain. Finally, we also described several specific studies involving specific entities inside the library supply chain.